Understanding implementation and improving nutrition interventions: Barriers and facilitators of using data strategically to inform the implementation of maternal nutrition in Uttar Pradesh, India - Young, Melissa F.; Bootwala, Ahad; Kachwaha, Shivani; Avula, Rasmi; Ghosh, Sebanti; Sharma, Praveen Kumar; Shastri, Vishal Dev; Forissier, Thomas; Menon, Purnima; Nguyen, Phuong Hong (Oxford University Press, 2021)
Background: In response to the high levels of maternal nutrition in Uttar Pradesh, Alive & Thrive (A&T) aimed to strengthen the delivery of nutrition interventions through the government antenatal care platform, including leveraging ongoing data collection to improve program delivery and reach (clinicaltrials.gov NCT03378141). However, we have a limited understanding of providers’ experiences and challenges of collecting and using data for decision making. Objective: To identify barriers and facilitators to the 1) collection of data and 2) use of data for decision-making. Methods: In-depth interviews (N = 35) were conducted among block-level government staff, frontline worker (FLW) supervisors and A&T staff in two districts in Uttar Pradesh. Systematic coding of verbatim transcripts and detailed summaries were undertaken to elucidate themes related to data collection and use. FLW supervisors (N = 103) were surveyed to assess data use experiences. Results: Data were used to understand the reach of maternal nutrition services, estimate the demand for supplements and guide identification of areas of low FLW performance. About half of supervisors reported using data to identify areas of improvement; however, only 23% reported using data to inform decision-making. Facilitators of data collection and use included collaboration between health department officials, perceived importance of block ranking and monthly review meetings with staff and supervisors to review and discuss data. Barriers to data collection and use included human resource gaps, inadequate technology infrastructure, FLW education level, political structure and lack of cooperation between FLWs and supervisors. Conclusions: Use of data for decision-making is critical for supporting intervention planning and providing targeted supervision and support for FLWs. Despite intensive data collection efforts, the use of data to inform decision-making remains limited. Collaboration facilitated data collection and use, but structural barriers such as staff vacancies need to be addressed to improve the implementation of maternal nutrition interventions.